2002
DOI: 10.1212/01.wnl.0000036566.00866.26
|View full text |Cite
|
Sign up to set email alerts
|

Axonal damage in the spinal cord of MS patients occurs largely independent of T2 MRI lesions

Abstract: Marked axonal loss occurs in MS spinal cords, largely independent of the degree of signal abnormality on T2-weighted MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 18 publications
13
81
0
Order By: Relevance
“…A complicated pattern of change in diffusivities may occur due to axonal loss [147] or an increase in axonal diameter. This was supported by previous findings in post--mortem MS spinal cord studies which showed areas of T 2 WI hyperintensities [148]. For areas containing crossing fibers, abnormal changes to the FA, AD and RD must be carefully assessed as MS pathology in these areas can produce unexpected results such as an apparent increase in diffusion anisotropy [133].…”
Section: Figure 8 Assessment Of Optic Nerve Degeneration In Eae--micsupporting
confidence: 79%
“…A complicated pattern of change in diffusivities may occur due to axonal loss [147] or an increase in axonal diameter. This was supported by previous findings in post--mortem MS spinal cord studies which showed areas of T 2 WI hyperintensities [148]. For areas containing crossing fibers, abnormal changes to the FA, AD and RD must be carefully assessed as MS pathology in these areas can produce unexpected results such as an apparent increase in diffusion anisotropy [133].…”
Section: Figure 8 Assessment Of Optic Nerve Degeneration In Eae--micsupporting
confidence: 79%
“…22,41 Although the sensitivity of spinal cord MR imaging is high, the relation between MR imaging and clinical findings remains poor. As already demonstrated by several brain studies, MR imaging parameters (like T2, T1, but also magnetization transfer ratio) in the spine also correlate better with demyelination than with the axonal disease, [41][42][43] which is the most direct cause of disability in patients with MS.…”
Section: Discussionmentioning
confidence: 61%
“…Such technologic advancements offer unprecedented resolution of micron-sized axons (12,16) in the living human brain. We hypothesized that MS lesions on high-gradient-diffusion MR images obtained by using a gradient strength of up to 300 mT/m would show decreased axon density and increased axon diameter, as has been shown in prior histopathologic studies (17)(18)(19). The purpose of this study was to evaluate the ability of high-gradient-diffusion MR imaging using gradient strengths of up to 300 mT/m to characterize axonal disease in lesions and normal-appearing white matter (NAWM) in patients …”
Section: Discussionmentioning
confidence: 97%